Impact of Radiotherapy Treatment on Jordanian Cancer Patients’ Quality of Life and Fatigue - Abu Obead, Kholoud; Batiha, Abdul-Monim Mohammad; Al-Jauissy, Mohammed Said; Alhalaiqa, Fadwa; AlBashtawy, Mohammed (International Journal of Advanced Nursing Studies, 2013)
Background: The distressing treatment of cancer whether chemotherapy or radiotherapy is associated with fatigue and has negative impact on patient quality of life (QOL). Objectives: The purposes of this study were to examine the impact of radiotherapy treatment on Jordanian cancer patients’ QOL and fatigue, and to explore the relationship between fatigue and QOL. Methods: One group quasi-experimental correlational design was used with 82 patients who had been diagnosed with cancer and required radiotherapy treatment. QOL was measured using the Functional Assessment of Cancer Therapy-General (FACT-G). Fatigue was measured using Piper Fatigue Scale (PFS). Data were collected over a period of three months, and analyzed using Pearson Product Moment Correlation, descriptive statistics and paired-sample t-test. Results: Significant differences were found between pre- and post- radiotherapy QOL mean total scores (t=19.3, df=79, P<0.05), as well as physical, emotional, sexual, and functional wellbeing dimensions. Statistically significant differences were found between pre- and post- radiotherapy fatigue mean total scores (t=-8.95, df=79, P<0.05), as well as on behavioral, affective, sensory, and cognitive dimensions of PFS. Quality of life total scores correlated significantly and negatively with total fatigue scores (P<0.01). Conclusions: Exposure of cancer patient to radiotherapy treatment increased their fatigue level and decreased their QOL. Nurses should assess cancer patients before, during, and after their treatment to design proper interventions to reduce fatigue and enhance QOL.